‘Respect’ and ‘self-determination’ women entrepreneurs’ identities and entrepreneurial discourses - Fernandes, Maria Emília Pereira (2017)
In order to understand how women entrepreneurs enact or challenge gender discrimination, research on entrepreneurship has focussed on the concept of identity (Bruni et al., 2004; Lewis, 2013; Orser et al., 2011; Patterson et al., 2012). Here, Identity is conceptualized as a dynamic effect of the gender constrains with which women entrepreneurs deal in their particular contexts (Bruni et al., 2004). However, this line of research (e.g. Díaz- García and Welter, 2010; Pettersson and Cassel, 2014; Maden, 2015; Lewis, 2013) has not explored the distinctions of women’s identities according to their business backgrounds, and how women with identical backgrounds collectively construct their entrepreneurial identities, when they have the opportunity to interact with each other and share their experiences.